From Ghanaian Modernist Painting Genre to Contemporary Functionality: A Spotlight on Samuel Prophask Asamoah - Adom, Dickson; Osei, Mavis; Adu-Agem, Joe (Journal of Urban Culture Research, 2020)
This is a biographic study of Samuel Prophask Asamoah, one of Ghana’s remarkable artists. It was aimed at showing how his philosophy and technique of painting are influenced by the early Ghanaian modernist painting genre while explaining how his themes reflected contemporary functionality in Ghana. The Feldman system of criticism guided the scholarly analysis of five selected paintings of Asamoah to unearth their contemporary significance. Personal interviews with Asamoah, as well as the intelligent comparison of his works with his contemporaries and other published scholarly literature, pivoted the intellectual discussions of his skillfully executed paintings. The discussions revealed that Asamoah’s paintings present the developmental challenges in Ghana and also offer solutions to them. His style of painting demonstrates that the Ghanaian modernist painting genre still exerts a strong influence on some young artists despite the radical changes seen in the art of the contemporary over the last two decades.